Distingsi Corak Tafsir Al-Munir Karya Wahbah Al-Zuhaili Dan Al-Tahrir Wa Al-Tanwir Karya Muhammad Al-Thahir Ibn Asyur - M.Syahbana Al Fatih; Sapa Anjila Madaniah; Ahmad Dasuki (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study examines methodological and stylistic distinctions between Wahbah al-Zuhaili’s Tafsir al-Munir and Muhammad al-Tahir Ibn ‘Ashur’s al-Tahrir wa al-Tanwir as two major twentieth-century Qur’anic commentaries. It assumes that the Qur’an’s ongoing relevance to modern problems depends on how exegetes manage linguistic meaning, contextual information, and the derivation of normative guidance for law and society. Using library research and comparative textual analysis, the study maps each work’s tahlili structure, linguistic tools, selection of contextual reports, and patterns of legal and ethical inference. Findings indicate that al-Zuhaili foregrounds a systematic, application-oriented fiqhi and socio-literary approach, while Ibn ‘Ashur emphasizes rational-linguistic argumentation and maqasid-based reading to articulate universal values. The study argues that the two approaches are complementary: al-Munir is strong for practical normative needs, whereas al-Tahrir wa al-Tanwir excels in deep semantic analysis and purposive interpretation. It recommends selective use according to issue type. This comparison supports balanced contemporary exegetical choices.